Physiotherapy-assisted prone or modified prone positioning in ward-based patients with COVID-19: a retrospective cohort study. (March 2022) - Tatlow, Claudia; Heywood, Sophie; Hodgson, Carol; Cunningham, Georgina; Conron, Matthew; Ng, Hui Yi; Georgiou, Harry; Pound, Gemma
Abstract: Objectives: To evaluate short-term change in oxygenation and feasibility of physiotherapy-assisted prone or modified prone positioning in awake, ward-based patients with COVID-19. Design: Retrospective observational cohort study. Setting: General wards, single-centre tertiary hospital in Australia. Participants: Patients were included if ≥18 years, had COVID-19, required FiO2 ≥ 0.28 or oxygen flow rate ≥4 l/minute and consented to positioning. Main outcome measures: Feasibility measures included barriers to therapy, assistance required, and comfort. Short-term change in oxygenation (SpO2 ) and oxygen requirements before and 15 minutes after positioning. Results: Thirteen patients, mean age 75 (SD 14) years; median Clinical Frailty Scale score 6 (IQR 4 to 7) participated in 32 sessions of prone or modified prone positioning from a total of 125 ward-based patients admitted with COVID-19 who received physiotherapy intervention. Nine of thirteen patients (69%) required physiotherapy assistance and modified positions were utilised in 8/13 (62%). SpO2 increased in 27/32 sessions, with a mean increase from 90% (SD 5) pre-positioning to 94% (SD 4) (mean difference 4%; 95%CI 3 to 5%) after 15 minutes. Oxygen requirement decreased in 14/32 sessions, with a mean pre-positioning requirement of 8 l/minute (SD 4) to 7 l/minute (SD 4) (mean difference 2 l/minute; 95%CI 1 to 3 l/minute) after 15 minutes. In three sessions oxygen desaturation and discomfort occurred but resolved immediately by returning supine. Conclusion: Physiotherapy-assisted prone or modified prone positioning may be a feasible option leading to short-term improvements in oxygenation in awake, ward-based patients with hypoxemia due to COVID-19. Further research exploring longerterm health outcomes and safety is required.